Teacher's emotional approach to students in Monsieur Lazhar film and film La Cour de Babel - Dian Savitri; Yohana Maria Monalisa; Yunilis Andika (Program Studi Pendidikan Bahasa Prancis FBS UNJ, 2022)
This research aims to determine the types of teacher's emotional approach to students in the film Monsieur Lazhar and the film La Cour de Babel. This study uses a descriptive qualitative approach which explains the types of emotional approaches according to Chevalier in his book entitled Faire Face Aux Emotions: Pour Gérer Au Quotidien Conflits, Stress, Agressivité (2007). There are six (6) types of emotional approach: 1) Recevoir 2) Supporter 3) Permettre 4) Aider 5) Apaiser and 6) Reparer. Then it is summarized again into four (4) types of emotional approaches: 1) Recevoir 2) Supporter et Aider 3) Permetre and 4) Asurer. Data analysis techniques in this study used data analysis techniques from Miles & Huberman which consisted of four (4) stages: 1) data collection, 2) data reduction, 3) data presentation and 4) conclusion/verification. The amount of data obtained from the results of the analysis is thirty eight (38) data contained in the conversations between teachers and students in the film Monsieur Lazhar and the film La Cour de Babel. The most common type of emotional approach was found in Asurer with nineteen (19) data, Supporter et Aider with nine (9) data, then Permettre with seven (7) data, and Recevoir with three (3) data.